DIAGNOSIS OF FINANCIAL STRENGTH OF JSC «KREDOBANK» - Grudzevuch, U.; Drozd, A. (Socio-economic relations in the digital society, 2021)
To achieve the financial stability of the bank it is necessary to constantly analyze its current state and planned indicators, taking into account endogenous and exogenous factors. In this context, the financial stability of JSC Kredobank and the factors influencing it were studied using the modern Z-score methodology, which has long been actively used by central banks of many countries and scientists of the International Monetary Fund, but has not yet gained proper recognition in financial sustainability in Ukraine. Based on the financial statements of JSC «Kredobank» built a logistics model that is characterized by high quality and is adequate. The set of financial indicators has been developed and used to calculate logistic regression that comprehensively reflect the financial condition of the institution and allow to predict the probability of its bankruptcy, which, in turn, will increase the efficiency of management decisions to identify crises and prevent their development. This logit model can be used both in the practice of financial management of the banking institution itself and in supervisory activities in the banking sector. It was found that the rise of COVID-19 slightly shook the level of financial stability of JSC «Kredobank» in 2020, so for further development and growth of profitability of the institution proposed a number of recommendations. It is determined that the quality of resources and capital are the main indicators of the bank’s efficiency, it is their optimal ratio in terms of solvency, liquidity, profitability and financial stability increases customers and, consequently, increases the income of the banking institution.